Efektivitas Senam Dismenore dan Musik Klasik Terhadap Penurunan Dismenore Pada Remaja - Nurmala Djimbula; Juda Julia Kristiarini; Yustina Ananti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Background: Dysmenorrhea is pain or cramps in the lower abdomen during menstruation. The impact of dysmenorrhea that occurs in adolescents can interfere with daily activities. Efforts to overcome dysmenorrhea can be made pharmacologically and non-pharmacologically. Providing dysmenorrhea exercise therapy and Mozart classical music can help reduce pain non-pharmacologically. Objective: This study analyzed the effectiveness of dysmenorrhea exercise and classical music in reducing dysmenorrhea in adolescents. Method: quasi-experiment with two groups pretest-posttest design. Using purposive sampling, the number of samples was 92 people, which were divided into 46 dysmenorrheal gymnastics teenagers and 46 classical music teenagers. Data analysis using Wilcoxon and Mann-Whitney. Results: Wilcoxon test obtained an average before and after dysmenorrhea exercise -a value of 0.000 <0.05, and classical music -a value of 0.000 <0.05. based on the Mann-Whitney test, it was found that the average after being given dysmenorrhea exercise and classical music showed a -value (0.313 > 0.05), meaning that there was no significant difference in the decrease in dysmenorrhea between gymnastics and classical music after being given treatment to adolescent girls. Conclusion: Dysmenorrhea gymnastics and classical music are equally effective in reducing dysmenorrhea.